Optimization of investment portfolio management - Oliinyk, Viktor; Kozmenko, Olga (Serbian Journal of Management, 2019)
The task of creating an investment portfolio by a financial institution is considered. Funds for creating a portfolio are taken from two sources: enterprise’s equity funds and borrowed funds. Optimization of the created portfolio is performed. A portfolio of maximum efficiency was obtained with restriction on the measure of risk, which is specified in the form of a VaR indicator. Using optimization portfolio data, a model of portfolio asset management is being built. Using the Pontryagin maximum principle, optimal strategies of its participants are determined. The optimal function of managing the investment portfolio in the form of a share of the income received is found. Numerical results of optimal management of investments in a financial portfolio from the financial institution as well as from the creditor are presented.